2022
DOI: 10.1038/s41467-022-32525-4
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmions in synthetic antiferromagnets and their nucleation via electrical current and ultra-fast laser illumination

Abstract: Magnetic skyrmions are topological spin textures that hold great promise as nanoscale information carriers in non-volatile memory and logic devices. While room-temperature magnetic skyrmions and their current-induced motion were recently demonstrated, the stray field resulting from their finite magnetisation and their topological charge limit their minimum size and reliable motion. Antiferromagnetic skyrmions allow to lift these limitations owing to their vanishing magnetisation and net zero topological charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…Many experiments have demonstrated that spin torque can not only be used to transport skyrmions but also to facilitate the creation of skyrmions. [29,[41][42][43][44][45][46][47][48][49][50][51][52] Therefore, the FM/HM structures capable of generating SOT by injecting currents in HM layers are potential candidates for skyrmion applications due to their convenience of both creating and manipulating skyrmions. Current flows with inhomogeneous density due to geometric confinement in tracks and specially engineered injector structures can be used to create skyrmions in multilayer thin films.…”
Section: Nucleation Of Skyrmions By Current and Electric Field Pulsesmentioning
confidence: 99%
“…Many experiments have demonstrated that spin torque can not only be used to transport skyrmions but also to facilitate the creation of skyrmions. [29,[41][42][43][44][45][46][47][48][49][50][51][52] Therefore, the FM/HM structures capable of generating SOT by injecting currents in HM layers are potential candidates for skyrmion applications due to their convenience of both creating and manipulating skyrmions. Current flows with inhomogeneous density due to geometric confinement in tracks and specially engineered injector structures can be used to create skyrmions in multilayer thin films.…”
Section: Nucleation Of Skyrmions By Current and Electric Field Pulsesmentioning
confidence: 99%
“…However, ferromagnetic skyrmions show an undesired skyrmion Hall effect, leading to an additional transverse motion toward the edges of the nanotrack, which is believed to be detrimental for applications such as skyrmion racetrack memory. , It is suggested that the skyrmion Hall effect can be suppressed in ferrimagnet-based multilayers. Specifically, ferrimagnetic skyrmions with reduced net magnetization exhibit a nearly vanishing skyrmion Hall angle and fast current-driven dynamics. , Along this intriguing direction, important progress has been made. …”
Section: Introductionmentioning
confidence: 99%
“…These systems allow skyrmions to be stabilized at room temperature, which is a fundamental requirement for practical applications. Lately, skyrmions have been reported in a variety of thin film materials, including HM/single-layer FM/oxide [11][12][13], HM1/FM/HM2 multilayers [14][15][16][17][18][19][20][21], HM/ferrimagnet/oxide multilayers [22,23], synthetic antiferromagnets (SAFs) [24][25][26], as well as bulk systems [27,28].…”
Section: Introductionmentioning
confidence: 99%